Investigation of The Use of Presentation Applications in Training Activities: A Systematic Literature Review - Waritsman, Arsyil; Arif Ahmad Djalaludin; Yonesi, Devi; Bambang Niko Pasla (Jurnal Prajaiswara, 2023)
Introduction/Main Objectives: This article was prepared with the aim of comprehensively investigating the use of presentation applications and their usefulness in training activities. Background Problems: The use of presentation applications plays an important role in training activities as part of human resource development. On the other hand, studies on the use of presentation applications in training activities have not been widely carried out. Novelty: This article provides the results of an investigation in the form of a literature study that can add insight regarding the development of the use of presentation applications in training activities and contains recommendations for further studies regarding the use of presentation applications in a more specific and in-depth manner. Research Methods: This study uses a systematic literature review method. Finding/Results: The findings from this literature study include (1) the most popular applications used in training activities are Microsoft PowerPoint; (2) in its development, presentation applications have been implemented, developed as learning media in training activities and the use of presentation applications in training runs effectively and (3) The use of presentation applications has benefits in training because learning becomes easier to understand, more interesting and pleasant. Conclusion: In general, the main contribution of this article is that investigations about the use of presentation applications and their usefulness in training activities are interesting and promising things to always study because this is very closely related to human resource development.